Contribution to the genomic study of the demographic and adaptive history of cattle and sheep populations in the Indian Ocean - (:unkn) unknown (My University, 2021)
The Indian Ocean represents a central migration zone for bovine (Bos taurus) and ovine (Ovis aries) populations accompanying human populations between East Africa, the Middle East and Southeast Asia, but their genetic diversity as well as their demographic and adaptive histories remain poorly known.The main objective of the thesis was to study the demographic and adaptive histories of cattle and sheep in the Indian Ocean, based on medium and high density genotyping data, with particular attention to the breeds of the western part of the zone located on the island of Mayotte, in the Comoros (never before phenotypically and genetically characterized) and on the island of Madagascar.For this purpose, a first phenotypic characterization was conducted on the sheep and cattle populations of Mayotte, allowing to highlight their phenotypic heterogeneity and to contribute to the recognition of the Zebu breed of Mayotte as a local French breed. This phenotypic characterization revealed a malformation of the external ear in 20% of the studied sheep, which present reduced or totally atrophied ears (microtia).The study of SNP-HD data of current cattle from Mayotte and Madagascar by comparing them to those of a larger panel of breeds representative of the bovine genetic diversity of the world allowed to highlight a great genetic proximity (predominantly indicine ancestry and weak African taurine ancestry) between these two breeds, having diverged in the 16th century, at the time of the arrival of the Europeans.Their common ancestral population is the result of a crossbreeding event involving an African zebu population (African taurine x zebu) and an Indian index population dating back to the 12th century.A sharp increase in the size of the estimated populations is observed between the 16th and 17th centuries and coincides with the expansion of the livestock trade to supply European ships in particular.The origin of the cattle populations of the western Indian Ocean
Keywords: African Research